Henry James and the Past - Bell, Ian F. A. author. aut Link
XII, 270 p.
Keywords: An examination of the work of Henry James. Topics covered range from commodity and style in "Washington Square", to the peculiarity of social life in "The Bostonians". Other works by the author include "Ezra Pound: Tactics for Reading" and "Henry James's Fiction as History".